Mithila Women in the Past and Present: A Journey of Resilience and Transformation (Patan Prospective Journal, 2024)
This paper explores the multifaceted journey of Mithila women, tracing their evolution from historical to contemporary times. Situated in the culturally rich region of Mithila, spanning parts of Northern India and Nepal, these women have been the custodians of a profound heritage characterized by resilience and adaptability. The paper delves into their roles within traditional societal frameworks, where they have long been pivotal in maintaining cultural practices such as the renowned Madhubani art. Through examining historical texts, cultural studies, and contemporary research, this study highlights Mithila women's enduring strength and agency. Despite rigid patriarchal structures and socio-economic challenges, Mithila women have continually carved out spaces for self-expression and empowerment. The paper investigates the transformative impact of education, economic participation, and political involvement on their lives. It emphasises how access to education has not only enhanced their capacities but also contributed to the socio economic development of their communities. The rise of Mithila women in local governance and their increasing role in Panchayati Raj institutions signify a shift towards greater political empowerment and social change. Ultimately, this paper aims to contribute to the broader discourse on gender and development by offering insights into the unique experiences of Mithila women. It underscores their journey of resilience and transformation as a testament to their enduring spirit and as a critical aspect of the region's socio-cultural fabric. The study calls for sustained efforts to address the challenges faced by Mithila women and to support their ongoing journey towards equality and empowerment.